On the demand for telemedicine: Evidence from the Covid-19 pandemic - Matias Busso; María P. González; Carlos G. Scartascini (Inter-American Development Bank (IDB), 2021)
Telemedicine can expand access to health care at relatively low cost. Historically, however, demand for telemedicine has remained low. Using administrative records and a difference-in-differences methodology, we estimate the change in demand for telemedicine experienced after the onset of the COVID-19 epidemic and the imposition of mobility restrictions. We find a 233 percent increase in the number of telemedicine calls and a 342 percent increase in calls resulting in a medication being prescribed. The effects were mostly driven by older individuals with pre-existing conditions who used the service for internal medicine consultations. The demand for telemedicine remains high even after mobility restrictions were relaxed, which is consistent with telemedicine being an experience good. These results are a proof of concept for policymakers willing to expand access to healthcare using advances in technology.
Keywords: I11; I15; P36; 330; Coronavirus; COVID-19; Health care demand; Telemedicine; Argentina